Using Pelvic Area Measurements In The Selection Of Replacement Sussex Heifers - Bila, Lubabalo (My University, 2019)
The aim of this study was to use pelvic area measurements and external body measurements in the selection of replacement Sussex heifers to reduce dystocia during parturition, while improving their ease of calving. A total number of one hundred and eighty-six (186) first calf Sussex heifers ca 24 months old, weighing approximately 350 kg were used for this study. All heifers used for the study had a good body condition score (BCS) with an average of three and weighed more than 65% of the mature female body weight of the Sussex breed. Six two-year-old bulls, weighing approximately 800 kg were used for mating the 135 heifers during the first trial and with a bull ratio of (1:35; 1:35; 1:35 and 1:30). The second trial consisted of 51 heifers with a bull ratio of 1:30 and 1:21. All the bulls were tested for fertility by a private veterinarian before the breeding season. A phenotypic negative correlation was found between CES and PA, r = -0.26 and a moderate negative correlation between CES and PH, r = -0.40. There was a significant correlation between CES and calf gender, r = -0.35. The chances of a heifer to experience dystocia were more when a male calf was born compared to female calves. Birth weight, which is regarded as a good indicator of calf size revealed a positive correlation with CES, r = 0.31, this showing that the higher the BW, the higher the probability of a heifer to experience dystocia. The R2 value of 0.34 indicated that approximately 34% of the variability in PA could be predicted by the chest depth of heifers. It can be concluded that pelvic measurements in Sussex heifers may be a valuable tool to reduce dystocia.
Dissertation
Keywords: Body measurements; Dystocia; Calving ease; Pelvic dimensions